Answer:
[ 5 ] -350 = 10x
[ 1 ] - 5 - 2 = ∛(10x + 7) + 2 - 2
[ 6 ] - 35 = x
[ 4 ] - 343 - 7 = 10x + 7 - 7
[ 3 ] - 343 = 10x + 7
[ 2 ] -7 = ∛(10x + 7)
Step-by-step explanation:
The given equation is
![-5=\sqrt[3]{10x+7}+2](https://img.qammunity.org/2023/formulas/mathematics/college/52anetqx62wq92l3att08u17pg04jcubqf.png)
To solve the expression, we first need to subtract 2 from both sides
![\begin{gathered} -5-2=\sqrt[3]{10x+7}+2-2 \\ -7=\sqrt[3]{10x+7} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a8xn8g3iaanmtygkn9gim0bpp4hrko792k.png)
Then, make each side to the power of 3, so
![\begin{gathered} (-7)^3=(\sqrt[3]{10x+7})^3 \\ -343=10x+7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kxy6ux75xgw1hyfj2q46ge48z23nze6uws.png)
Subtract 7 from both sides
![\begin{gathered} -343-7=10x+7-7 \\ -350=10x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l9ml3uzihylkv6l6lrq9snsdbdml1c7vav.png)
Divide both sides by 10
![\begin{gathered} -(350)/(10)=(10x)/(10) \\ -35=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/46orxqbu1qj6hysyb8i0v1cbhargbdq5cd.png)
Therefore, the order of the steps is
[ 5 ] -350 = 10x
[ 1 ] - 5 - 2 = ∛(10x + 7) + 2 - 2
[ 6 ] - 35 = x
[ 4 ] - 343 - 7 = 10x + 7 - 7
[ 3 ] - 343 = 10x + 7
[ 2 ] -7 = ∛(10x + 7)